Cardboard Architecture: Eight Decades of Exploration in Academic Research and Professional Practice 1940-2019 - Diarte, Julio; Shaffer, Marcus (Enquiry The ARCC Journal for Architectural Research, 2021)
Explorations in the use of cardboard products in architecture exist since the 1940s. However, it was not until the early 1990s, when Shigeru Ban’s work emerged when cardboard products became a potential material for architecture. Since then, cardboard use in architecture has been continuously growing worldwide, and Ban’s cardboard buildings have now achieved important recognition. This article reviews cardboard architecture works in academic research and professional architectural practice in the last eight decades to lay a foundation for designers to get ahead in cardboard for architecture. Cardboard products could contribute to increase more environmentally friendly and affordable architecture because they are recyclable, low-priced, and have relatively good strength to sustain loads, among other potential advantages for construction. The study summarizes the fundamentals of cardboard architectural design and diverse strategies proposed by different authors to decrease cardboard strength degradation due to the material’s weaknesses.